Assessing the individual anaerobic threshold: The mathematical model - Machado, L.; Almeida, M.; Morais, P.; Fernandes, R.; Vilas-Boas, J. P. (Biomechanics and Medicine in Swimming X, 2006)
This work presents a mathematical method based on a fit to the observed velocity/[La-] data points for swimmers that allows the determination of the anaerobic threshold individually. In the present method a straight line is fitted to the lower velocity data points, while an exponential line is fitted to the higher velocity data points. The point of interception of both lines is considered as the point of beginning of the anaerobic threshold. Some practical examples are shown.